The effects of rule changes on basketball game results in the men`s European Basketball Championships - Pluta, B.; Andrzejewski, M.; Lira, J. (Human Movement, 2014)
Purpose. The aim the study was to analyze the effects of rule changes in men`s professional basketball. Univariate analysis examined game statistics, concentrating only on points scores from selected basketball games and did not include situational variables that may have affected game dynamics. Methods. Data on the results of all games played in the men`s European Basketball Championships between 1935 and 2013 were collected and subjected to statistical analysis. Six main rule modifications which directly affected game play were identified in chronological order. Results. The number of points scored and allowed changed significantly after 1956. The greatest changes in game scores as a result of rule modifications were after rule changes in 1956 and after 1984. Conclusions. Rule changes involve processes that modify game conditions and should be validated following reflective analysis.